A Duration Analysis of Terrorist Strategy in Domestic Conflict: Evidence from Northern Ireland 1971 - 1994 - Neil Ferguson (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper employs a dataset from The Troubles in Northern Ireland to empirically test the interactions of terrorists operating in domestic conflicts. Specifically, it assesses the theoretical claims that organisations 'match' strategies, choosing their action according to the activity of their rivals. By employing duration analysis, I also test the implications of the qualitative literature specific to this conflict. I test the suggestion that Loyalists acted as a reactive force, aiming to deter Republican attacks on Northern Ireland's Protestant community. Republicans are claimed to have operated a broader strategy, aimed at imposing maximum physical and psychological damage. The results present evidence that supports these qualitative writings, whilst showing that organisations operated different strategies in different locations and at different times. By mapping the conflict to Northern Ireland's Westminster parliamentary constituencies, I also provide evidence that interaction occurred locally, rather than nationally, which reflects the organisational structure of the Loyalist organisations.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330